Aggregate earnings and macroeconomic shocks: The role of labour market policies and institutions - Andrea P. Bassanini (Institute for the Study of Labor (IZA), 2012)
I examine the effect of labour market policies and institutions on the transmission of macroeconomic shocks to the labour market, using both aggregate and industry-level annual data for 23 OECD countries, 23 business-sector industries and up to 29 years. I find that high and progressive labour taxes and generous unemployment benefits amplify labour income fluctuations. By contrast, statutory minimum wages reduce the difference in the sensitivity of wages to aggregate shocks between low-wage and high-wage industries. Dismissal regulations are found to mitigate the impact of shocks on both earnings and employment. Moreover, this mitigation effect is greater in industries where firms have a greater propensity to make staffing changes through dismissals.
Keywords: J21; J31; J60; 330; employment fluctuations; business-cycle; EPL; tax wedge; unemployment benefits; Arbeitsmarkt; Arbeitsmarktpolitik; Konjunktur; Schock; Arbeitsmarktflexibilität; OECD-Staaten